Responding to the West Essays on Colonial Domination and Asian Agency - Hägerdal, Hans (ICAS Publications Series, 2009)
The nine essays of this volume, spanning from the eighteenth to mid-twentieth century, highlight the workings of, and reactions to, colonial domination in Asian contexts. The scholars, which include Victoria Haskins of the University of Newscastle, use a range of social science history methods to explore new paths to colonial history. How were individuals, groups, and social categories able to order their lives in the face of the implementation of external dominance? In other words, what was the agency enabling them to interact with, adapt to, use, counteract and in the end defeat colonialism? The essays emphasize colonialism as a multifaceted historical phenomenon which has taken a number of mutually incompatible forms. The various texts thus reflect on both the "early" colonialism build on indirect and informal practices, and the later forms marked by a high degree of authoritarian control.